The fractured rocks. - Stournaras, G.; Migiros, G.; Stamatis, G.; Evelpidou, N.; Botsialas, C.; Antoniou, B.; Vassilakis, E (International Association of Hydrogeologists - IAH, SP (Special Publication) the Groundwater in Fractured Rocks International Conference, 2007)
The present contribution is dealing with the outcrops and the hydrogeological behaviour of the fractured rocks (mainly igneous, metamorphic and not karstified carbonate rocks, as they have been defined by the I.A.H Commission of the Hardrock Hydrogeology). The presentation starts with the description of the geotectonic regime of the Hellenic territory into the adopted different geotectonic zones. For each zone a general lithological and structural description is attempted accompanied by the description of the main aquifers and the general directions of the groundwater flow related to the formation of the rock mass fractures. Finally, an analytical description of some case studies is presented.